Al-Muwathanah Concept for non Muslims in Islamic majority Countries Siyasah Fikih Perspective - Lukman Arake (International Journal on Advanced Science, Education, and Religion, 2019)
The Islamic priests do not use the word of minority (akalliyah) in the literature of classical Islamic jurisprudence when they talk about the existence of non-Muslims in Islamic countries, but they use the term of ahluzzimmah. Their reason not to use that term is because Islam itself does not distinguish the rights and obligations between Muslims or non-Muslims who live in a country, except those closely related to religious issues. This was caused by the actualization concept from one of religion rule "lahum maa lana wa alaihim ma alaina" which means: they have rights and obligations as Moeslems. Despite our scholars do not use the term of minority in their own intellectual tradition, the term has become popular especially in a concept of writing process that cause the using of these terms is valid.